THE EFFECT OF TUINA MASSAGE USING VCO APPLICATION ON INCREASING THE APPETITE OF STUNTED TODDLERS - Tiwery, Indah Benita (Universitas Aisyah Pringsewu, 2024)
Introduction: Stunting is a chronic nutritional condition that describes the inhibition of growth and development due to long-term malnutrition. Lack of appetite is a trigger for chronic nutritional problems if left unchecked. The treatment option of non-pharmacological therapy tui na massage with virgin coconut oil is part of nursing care. Objective: This study was conducted to analyze the effect of tui na massage with virgin coconut oil application on increasing the appetite of stunted toddlers. Materials and Methods: This study used a quasi-experimental method with two group pre-post test on 30 stunted toddlers. The sample was taken with total sampling technique. Appetite of toddlers was measured using an appetite questionnaire. Data analysis using univariate, Wilcoxon test to analyze the effect of tui na massage with virgin coconut oil application on increasing the appetite of stunted toddlers. Results: Tui na massage with virgin coconut oil application has a significant effect on increasing the appetite of stunted toddlers with a value of p = 0.000. Conclusion: There is an effect of tui na massage intervention with virgin coconut oil application on increasing the appetite of stunted toddlers. Based on the conclusion, tui na massage with virgin coconut oil application can be used as a non-pharmacological therapy to overcome the problem of lack of appetite in toddlers.